P105 Ambulatory study center at the University of Basel Children's Hospital (UKBB). Issue 6 (17th May 2019) - Werner, C; Santoro, R; Bielicki, J
Abstract : Background: Many drugs authorized in Europe and the United States are inadequately studied in children. SwissPedNet Funding has boosted the development of specialized and professional pediatric centers for clinical studies in Switzerland tasked with executing compliant, reliable and family-centered clinical research. The University of Basel Children`s Hospital (UKBB) is one of the pediatric clinical study centers. Methods: The Department for Clinical Research in Basel consists of the study center for adults at University Hospital Basel (USB) and the Ambulatory Study Center (ASZ) focusing on pediatric studies at the UKBB. The latter was established in 2015, and consists of a specialized team, including a medical director, medical coordinator, medical specialists in pediatrics as well as a team of study nurses. The ASZ supports and promotes clinical studies with and for infants and children for external and internal sponsors in various therapeutic areas such as oncology, cardiology, pneumology, nephrology, neuropediatrics, orthopaedics and infectious diseases. The full range of activities for executing the approved clinical study protocol can be offered, including planning, implementation, budgeting, coordinating, monitoring and archiving as well as collaboration with all required hospital departments. Results: Up to now, the ASZ has enrolled around 600 children in clinical trials, with 6 studies completed and 12 studies ongoing. A comprehensive Quality Management system was established and SOPs were jointly created with the adult study center. A digital clinical study request form is available for sponsors via the website. Conclusion: We see an increased demand for pediatric clinical studies across all age ranges and therapeutic areas. We envision a center of excellence with a pool of fully trained study nurses to accommodate and centrally organize all pediatric studies in the UKBB. Parent engagement and patient inclusion is one critical step to further improving healthcare for pediatric patients through highest quality clinical research. Disclosure(s): Nothing to disclose